Food Fight!: Parenteral Nutrition, Enteral Stimulation and Gut-Derived Mucosal Immunity - Hermsen, Joshua L. (2008)
Nutrition support is an integral component of modern patient care. Type and route of nutritional support impacts clinical infectious outcomes in critically injured patients. This article reviews the relationships between type and route of nutrition and gut-derived mucosal immunity in both the clinical and laboratory settings.